Creating Places of Belonging: Expanding Notions of Permanency with Indigenous Youth in Care - de Finney, Sandrina; di Tomasso, Lara (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
This paper calls for creative pathways of engagement that delineate places of belonging for and with Indigenous youth in care. It draws on two community-based research studies conducted in British Columbia, with urban and off-reserve Indigenous youth to contextualize and extend understanding of permanency for Indigenous youth in care. Our discussion explores permanency in relation to both Western understandings of government care, guardianship, and adoptions, and Indigenous customary caregiving and cultural planning for cultural permanency, such as naming and coming home ceremonies, custom adoptions, and kinship care.